SUPPORTING FACTORS FOR PRIMARY SCHOOL TEACHERS IN ENSURING INCLUSIVE EDUCATION FOR CHILDREN WITH AUTISM SPECTRUM DISORDERS - Raudeliunaite, Rita; Steponėnienė, Eglė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The objective of the study presented in this article is to reveal supporting factors for primary school teachers in ensuring inclusive education for children with autism spectrum disorders (hereinafter the ASD). Qualitative research was chosen for the study. In the study, the method of a semi-structured written reflection was used. The obtained data was analysed by applying the content analysis method. Qualitative content analysis was carried out in accordance with the inductive, study data based and categories composed logic.16 primary school teachers participated in the study. The study data revealed that the school’s inclusive culture and organization of inclusive education by the teacher at the classroom level had a significant importance for ensuring inclusive education for children with ASD. The school’s openness to children diversity, implementation and cherishing of inclusive education values, favourable physical and psychosocial environment, ensuring support for learners, their parents, teachers and education support professionals, financial resources which allow for attracting necessary human and material resources, skilled teachers and professionals, the school’s collaborating community and the school’s collaboration with other institutions to ensure the quality of inclusive education were considered the key factors for the school’s inclusive culture. The teacher’s positive attitude to all the learners, child-oriented approach, favourable and inclusive educational and social environment created in the classroom, the teacher’s close collaboration with learner’s parents, other teachers and education support professionals, and continuous improvement of qualification were indicated as factors of the key importance for creation of an inclusive educational environment at the classroom level by teachers.